«Authoritarian Transition of Peripheral Countries of Interwar Europe: Politological Analysis» - E. G. Ponomareva (Vestnik MGIMO-Universiteta)
The author ponders on the causes of the crisis of democraticmodels in the countries of Central and Eastern Europe, South-East Europe and the Baltic states. Having analysed a complex of factors, she comes to the conclusion that the authoritarian transition of European peripheral countries in the interwar period (1918—1939) was appropriate. While all authoritarian regimes of the period in the region under study were characterized by three foundations of authoritarianism– Fuhrerprinzip, ideas of constructing nationstate and nationalism, specific traits allow to distinguish between three clusters of authoritarian regimes in the interwar Europe: military-bureaucratic, corporate (guild) and pre-totalitarian (fascist mobilization) ones. However, the main conclusion is: the complex economic, political and socio-cultural situation in the countries of Central and Eastern Europe, South-East Europe and the Baltic states aggravated by the consequences of globalization and world financial crisis is able to provoke recurrences of authoritarian transition.